IMPLEMENTASI DESIGN THINKING PADA DESAIN PROMOSI VISUAL SPANDUK UMKM RUMAH MAKAN TIGA PUTRI UNIVERSITAS RIAU (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
This study examines Rumah Makan Tiga Putri, a culinary business located near Universitas Riau that offers Minang dishes at affordable prices. Despite its strategic location and a market potential dominated by students, the business faces challenges in optimizing its marketing strategy, especially in visual media promotion. The promotional banner, which is unattractive and lacks clear information, reduces the effectiveness of visibility in attracting and engaging consumers. This study explains the implementation of the design thinking process in redesigning the promotional banner for Rumah Makan Tiga Putri. The purpose of this study is to describe the stages of design thinking in optimizing visual communication effectiveness to increase consumer reach and visibility. The research uses a descriptive qualitative approach by applying the stages of design thinking: empathize, define, ideate, prototype, and test. Data were collected through direct observation, interviews with owners and consumers, comparisons with academic colleagues, and questionnaires using a Likert scale to measure perceptions of the banner's visual aspects. The findings show that the implementation of design elements related to imagery, color, typography, information clarity, and the integration of visual elements with Minang cultural characteristics can improve visual communication effectiveness and strengthen brand identity. The proposed solution is a redesigned banner that is informative, aesthetically pleasing, and culturally representative of Minang identity. Positive responses from participants indicate that applying design thinking is effective in optimizing banner design as visual promotional media, improving visibility and accessibility of business information for potential consumers around the Universitas Riau area.
Keywords: banner design; business; design thinking; marketing strategy; visual promotional media